Effect of Variable Practice Schedules Accompanied by Some Educational Tools on Learning Number of Attack Skills in Basketball (College of Basic Education Research Journal, 2025)
• Know effect of variable practice schedules accompanied by some educational tools and  way followed in learning number of attack skills in basketball on  two groups of  research.• Preference between  control and experimental research groups in learning a number of offensive basketball skills as shown in  results of  post-test.Researchers assumed that:• There are significant differences between  pre- and post-test results of  control  and  experimental group in learning number of offensive skills in basketball and in favor of post-test results.Researchers used  experimental method with two equal groups. Research community was (190)  male and female students of  academic year (2023-2024) .  Research sample was (32) freshmen in Physical Education and Sport Sciences Department / College of Basic Education / University of Mosul in  academic year2023/2024. Two independent variables were given to two classrooms in a random way using  simple random draw, each group had (16) students. Control group studied traditionally depending on their professor while  experimental group studied according to variable practice schedules  accompanied by various educational tools. Educational curriculum contained (16) educational unit so that each group took (8) units. Time of each educational unit is (90) minutes.  Researchers concluded that:Experimental group that used variable practice schedules  accompanied by various educational tools out-performed  control group in learning number of offensive skills in basketball in  post-test results and   all other skills.